Emergence of Lyme Disease on the French Riviera, a Retrospective Survey - Sevestre, Jacques; Benichou, Antoine; Rio, Vanessa; Delaunay, Pascal; Gonfrier, Géraldine; Martaresche, Cécile; Carlo, Virginie; Nakam, Sarah; Mondain, Véronique; Carles, Michel; Jeandel, Pierre Yves; Durant, Jacques (Frontiers in Medicine, 2022)
Background The French Riviera has been declared free of Lyme Borreliosis (LB) for years. Many patients are referred for presumed LB, sometimes with atypical clinical signs and/or doubtful serology, calling the diagnosis into question. Methods Patients were assessed for LB diagnosis, depending on clinical presentation, laboratory findings, and further examination by other medical professionals. Results Among 255 patients, 45 (18%) were classified as confirmed LB cases [including 28 ongoing LB (10%) and 17 past LB (8%)], and for 210 (82%) a Lyme borreliosis diagnosis was ruled out. Among ongoing LB, 56% had been exposed to or bitten by ticks, exclusively in rural locations of the Alpes-Maritimes. As a result of the diagnostic procedure, 132 (52%) patients had been treated. An alternative diagnosis was established for 134 (52%) patients, covering a wide range of conditions, including mainly psychological (28%) and neurological conditions (25%) or inflammatory and systemic diseases (22%). Conclusions Our results strongly suggest the endemicity of LB in the Alpes-Maritimes region. Confirmed LB accounted for 18% of patients while 52% were diagnosed with other conditions.